2004
DOI: 10.4161/cc.4.2.1413
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 Signaling Promotes Tumor Growth in Colorectal Cancer

Abstract: Recent investigations support an important role for TGF-β in the development of colorectal cancer. However, the molecular consequences of TGF-β signaling in the colon remains incompletely understood. In a recent study in Immunity, we analyzed the role of TGF-β in a murine model of colon cancer. Using transgenic mice overexpressing TGF-β or a dominant negative TGF-β receptor II under control of the CD2 minigene, we show that TGF-β signaling in tumor infiltrating T lymphocytes regulates the growth of dysplastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
186
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(194 citation statements)
references
References 28 publications
7
186
1
Order By: Relevance
“…In a model developed in our laboratory, the conditional deletion of the SMAD4 gene specifically in T cells leads to a progressive intestinal epithelial hyperplasia (unpublished). We observe a significant increase in T-cell production of IL-6 in vivo and in vitro in this model, consistent with the transgenic model in which T-cell resistance to TGF-b is induced by a CD2-driven dnTbRII (Becker et al, , 2005. More importantly, we also see a significant production of IL-5, a key factor in the induction, activation, and migration of eosinophils.…”
Section: Smad-dependent Signaling In T Cells Controlling Mucosal Inflsupporting
confidence: 69%
See 1 more Smart Citation
“…In a model developed in our laboratory, the conditional deletion of the SMAD4 gene specifically in T cells leads to a progressive intestinal epithelial hyperplasia (unpublished). We observe a significant increase in T-cell production of IL-6 in vivo and in vitro in this model, consistent with the transgenic model in which T-cell resistance to TGF-b is induced by a CD2-driven dnTbRII (Becker et al, , 2005. More importantly, we also see a significant production of IL-5, a key factor in the induction, activation, and migration of eosinophils.…”
Section: Smad-dependent Signaling In T Cells Controlling Mucosal Inflsupporting
confidence: 69%
“…The broader influence of TGF-b in the immune system can in part be attributed to the interaction between intermediates in the TGF-b pathway with components downstream of both cytokine receptors and antigen receptors (Jacobsen et al, 1991), including Toll-like receptors (Moustakas and Heldin, 2003;Xiao et al, 2003), and modulation of cytokine production Roberts, 1997, 1998;Laouar et al, 2005;Lyakh et al, 2005). However, the recognition that a disruption or loss of TGF-b signaling within immune cells directly contributes to the initiation and progression of epithelial cancer highlights the role this cytokine plays in controlling cell-to-cell interactions, and the immune surveillance of cancer (Becker et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…The increased number of Th17 cells may aggravate inflammation and promote tumor growth by increasing IL-6 secretion (Gaffen 2008). On the other hand, IL-6 itself also has the capability to promote tumorigenesis (Becker et al 2005). Thus, we concluded that the serum IL-6 level might be a useful biomarker for predicting colorectal tumorigenesis and disease progression.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, we found IL-6 and ICAM1, which are upregulated only in high-risk tumors, as the key mediators of chemosensitivity. In good correlation, IL-6 and ICAM1 were found associated with invasion, angiogenesis, tumor growth, chemoresistance, and prognosis in many cancers (29)(30)(31)(32). .…”
Section: Discussionmentioning
confidence: 99%